Knowledge and Practice of Ethical Consideration for Quality of Research Skills among Graduate Students of Universities in Cross River State, Nigeria - Ubi, Isaac Ofem; Orji, Evelyn Ijeoma; Osang, Anastecia William (Richtmann Publishing, 2020)
This study is an assessment of knowledge and practice of ethical consideration for literacy in research among graduate students of the two Universities in Cross River State, Nigeria. The first was 214 graduate students’ who had defended proposals, while the second was 120 post field Theses. The two samples were selected through accidental technique from a population of 713 graduate students of the University of Calabar and the Cross River University of Technology who have at least defended their Thesis proposals. Results of the study indicate that only 47.31% of the students knew what ethical consideration meant in research with 83.52% of them emphasising confidentiality in their instruments. Only 33.86% and 26.17% emphasised voluntary participation and anonymity respectively. The study recommends the inclusion of ethical issues in university course outlines for research methods in education.